Women, Work, and Siyāsah Dustūriyyah: A Critical Review of Indonesia’s Job Creation Law - Citra Widyasari S; Afifah Faiqah (UIN Sunan Kalijaga Yogyakarta, 2023)
This article examines Law No. 6 of 2023 on Job Creation from the perspective of Islamic constitutional theory (siyāsah dustūriyyah) and the objectives of Islamic law (maqāṣid al-sharī‘ah), focusing on the protection of women workers’ rights. Although the law recognizes key protections—such as menstrual leave, maternity leave, and wage equality—its implementation is undermined by weak enforcement and structural gaps, particularly for women employed under short-term contracts, outsourcing schemes, or in the informal sector. Using a normative qualitative approach, this study evaluates the law’s normative substance against Islamic principles of social justice, protection of human dignity, and state responsibility toward vulnerable groups. The findings reveal a normative contradiction: while the law aligns with international standards such as CEDAW in form, it fails to offer substantive justice as required by Islamic constitutional ethics. The dominant emphasis on labor market flexibility and investment certainty diminishes state accountability and reinforces systemic discrimination against female workers. The study concludes that Law No. 6/2023 lacks a transformative vision for gender equity and fails to embody maqāṣid principles in legislative outcomes. It recommends policy reforms that integrate Islamic ethical frameworks into national labor law. Future research should adopt empirical methods to assess how current legal norms shape the lived experiences of women workers in Indonesia’s evolving labor landscape.. Abstrak Penelitian ini bertujuan untuk mengkaji Undang-Undang Nomor 6 Tahun 2023 tentang Cipta Kerja dari perspektif pemikiran ketatanegaraan Islam (siyāsah dustūriyyah) dan tujuan-tujuan hukum Islam (maqāṣid asy-syarī‘ah), dengan fokus pada perlindungan hak-hak buruh perempuan. Meskipun undang-undang ini secara normatif mengakui beberapa hak perempuan pekerja seperti cuti haid, cuti melahirkan, dan kesetaraan upah, implementasi dan pengawasan terhadap hak-hak tersebut masih lemah. Hal ini berdampak pada ketidakpastian perlindungan bagi perempuan yang bekerja dalam sistem kontrak jangka pendek, outsourcing, serta sektor informal. Secara teoritis, penelitian ini mengintegrasikan pendekatan normatif-kualitatif dengan kerangka siyāsah dustūriyyah dan maqāṣid asy-syarī‘ah untuk mengevaluasi sejauh mana UU No. 6/2023 mencerminkan prinsip keadilan substantif dalam Islam. Temuan utama menunjukkan bahwa undang-undang ini masih memprioritaskan efisiensi pasar daripada perlindungan kelompok rentan, sehingga bertentangan dengan mandat keadilan sosial dalam ajaran Islam. Negara dianggap gagal menjalankan tanggung jawab etisnya sebagai pelindung rakyat apabila membiarkan buruh perempuan berada dalam posisi subordinat. Penelitian ini merekomendasikan pembaruan kebijakan ketenagakerjaan yang tidak hanya berorientasi pada pertumbuhan ekonomi, tetapi juga berbasis pada nilai-nilai maqasid dan etika konstitusional Islam. Kajian lanjutan perlu memperluas pendekatan dengan metode empiris untuk menilai dampak nyata regulasi terhadap kesejahteraan perempuan pekerja di Indonesia